2012
DOI: 10.1021/ac3032788
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Microstructure of Heparin and Heparan Sulfate Using N-Sulfoglucosamine 1H and 15N NMR Chemical Shift Analysis

Abstract: Heparin and heparan sulfate (HS) are members of a biologically important group of highly anionic linear polysaccharides called glycosaminoglycans (GAGs). Because of their structural complexity, the molecular-level characterization of heparin and HS continues to be a challenge. The work presented herein describes an emerging approach for the analysis of unfractionated and low molecular weight heparins as well as porcine and human-derived HS. This approach utilizes the untapped potential of 15N NMR to characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 49 publications
2
28
0
Order By: Relevance
“…The modification of chitosan has been more widely explored and shown that optimization of the reaction time, temperature and pH can achieve degrees of sulfation in the range of 10% to 63% . Thus, the extent of sulfate derivatization of Ch‐Arg achieved in this study is closely aligned with that achieved for chitosan and is in the range of sulfate content of HS/heparin …”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The modification of chitosan has been more widely explored and shown that optimization of the reaction time, temperature and pH can achieve degrees of sulfation in the range of 10% to 63% . Thus, the extent of sulfate derivatization of Ch‐Arg achieved in this study is closely aligned with that achieved for chitosan and is in the range of sulfate content of HS/heparin …”
Section: Discussionsupporting
confidence: 62%
“…Heparin and HS are structurally similar linear polysaccharides composed of repeating disaccharide units of uronic acid and glucosamine . The residues can be sulfated at positions 2‐O and N on the uronic acid residues as well as the 3‐O and 6‐O positions on the glucosamine residues to produce HS/heparin substituted with sulfate groups in the range of 0%–55% . Growth factors bind to sulfated domains within HS/heparin chains, thus the density as well as overall level of sulfation is important for the fine tuning of growth factor binding and signaling .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, signal of C4 could be attributed to the resonance at 71.1 and 3.58 ppm. The occurrence of a strongly down-fielded signal at 77.4 ppm corroborated the substitution by a (OSO 3 ) -group (Langeslay et al 2013) in one of the carbons of the glycerol moiety. …”
Section: Sea Urchin Sperm and Egg Jelly Coat Contain Distinct Sialic mentioning
confidence: 53%
“…These have revealed several unusual features, which include the existence of equilibria between conformational states in the ring forms of iduronate residues (particularly idoA2S) of heparin (whose exemplars are the 4 C 1 , 1 C 4 and 2 S 0 forms [9]), changes in the glycosidic linkage geometry as a function of substitution pattern [10,11] and complex cation binding characteristics, which can also affect biological properties [6,7,[12][13][14][15][16]. Recently, however, several studies have also been undertaken in which one of the NMR active nitrogen isotopes ( 15 N) of glucosamine residues M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT has been measured, to provide additional structural details, particularly pertaining to the N-sulfamate substitution at position-2 in glucosamine residues [17][18][19][20][21].…”
Section: Resultsmentioning
confidence: 99%